Unusual complication of dental extraction: Lingual abscess - Lalee Varghese; Pratibha Agarwal; Vedantam Rupa (Wolters Kluwer Medknow Publications, 2013)
Acute lingual swelling is a potentially life threatening clinical condition which is encountered very rarely, the differential diagnosis of which includes hemorrhage, infarction, abscess, tumor and edema. Herein we report a case of lingual abscess that presented with acute tongue swelling and respiratory distress after extraction of lower two incisor teeth.